The Effect of Mutation and Work Environment on Employee Performance With Job Satisfaction as an Intervening Variable in Bpjs Employment Meulaboh Branch, Pematang Siantar Branch and Langsa Branch - HAIKAL NURSEHA; Kiki Farida Ferine (International Journal of Society and Law, 2024)
This research aims to see the influence of mutation and work environment on employee performance with job satisfaction as an intervening variable. With quantitative as the type of research, primary as the source and data collection is used by distributing questionnaires and Likert scales, the research population is 60 employees and the sample is also 60 employees because all the sampling techniques used are saturated sampling techniques. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Employee Performance with an original sample value of 0.443 and a p value of 0.000. Work Environment has a positive and significant effect on Job Satisfaction with an original sample value of 0.461 and a p value of 0.001. The work environment has a positive and significant effect on employee performance with an original sample value of 0.275 and a p value of 0.021. Mutations have a positive and significant effect on Job Satisfaction with a value of 0.443 and a p value of 0.002. Mutations have a positive and significant effect on employee performance with an original sample value of 0.239 and a p value of 0.032. The work environment influences employee performance indirectly through job satisfaction positively and significantly with an original sample value of 0.204 and a p value of 0.014. Mutations influence employee performance indirectly through job satisfaction with an original sample value of 0.196 and a p value of 0.010